Lessons learned in an inclusive classroom: a case study of differentiated instruction - Lange, Katherine, author; Banning, James, advisor (Colorado State University. Libraries, 2009)
The use of Differentiated Instruction, a teaching methodology that encompasses aspects of brain based learning, multiple intelligences and cooperative learning, is a term heard widely in the realm of education today. Although Differentiated Instruction is used in educational settings more and more, studies that have been conducted about its use have not looked at the issues raised by teachers when implementing Differentiated Instruction or the specific strategies that teachers find most useful when using this methodology. In this case study analysis, teachers were interviewed and observed over a semester at a high school in Western Colorado. The purpose of the study was to fill a gap in research that looks at how teachers at the high school level begin using this methodology in their classroom and the pros and cons of using this methodology in their classrooms when seeing upward of 150 students a day. Results showed that even though the teachers in the study found strategies that were differentiated in style helpful to them in their classrooms, daily activities that teachers must adhere to became trying and cumbersome. Activities that became more difficult when trying to differentiate included planning and management. Both teachers in the study reported feeling a bit overwhelmed when trying to meet the varying needs of the 150 kids that they saw in one given day. Planning lessons differentiated in style and managing students' behavior in the classroom when students were engaged in differentiated activities sometimes caused the teachers to feel anxious and overwhelmed. Benefits of differentiating instruction that were seen with the students included an increase in autonomy and self-esteem. The findings and themes that emerged from the study are similar to information disseminated by authors and researchers alike that have looked at Differentiated Instruction over the past several years.
Keywords: differentiated instruction; inclusion; multiple intelligences; case studies; teaching methods; instructional design